An investigation into the popularity of Zimbabwe's first health communication soap opera, Studio 263 : a qualitative reception study of Bulawayo students aged between 15 and 20 years - Bhebhe-Mpofu, Adilaid (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
Within the context of debates concerning the reception and interpretation of media texts by television audiences, this qualitative reception study explores how a sample of Bulawayo students negotiate meanings from Zimbabwe's first health communication soap opera, Studio 263. The study thus examines the reasons behind the popularity of this programme with this target audience. The findings of the study reveal that meaning making is a complex process that is dependent on a variety of factors which include, among others, the socio-cultural context of media consumption, gender, economic disposition and age. It particularly maintains that gender and lived realities influence the interpretation and negotiation of meanings in this particular study.,Adobe Acrobat Pro 11.0.0 Paper Capture Plug-in
Keywords: Studio 263 (Television program); Television soap operas -- Zimbabwe; Television viewers -- Zimbabwe; Mass media and children -- Zimbabwe; Television and children -- Zimbabwe; AIDS (Disease) -- Zimbabwe